(3cJGH GdCQHYjf GdEHOGd GdJSGYjGJs - (3CHh eMeO YHO GdeDef Hf Nda GdOejGWj, TQa GdOjf,J (B705 (3g` s
(3ChdgG (B:s
(3GdMeO ddg SGeY GdGUhGJ heLjH GdOYhGJ hbGVi GdMGLGJ GdMOjK GdChd Yf CfS Hf eGdc QVi Gddg Yfg bGd cGf QShd Gddg Udi Gddg Ydjg hSde GLed GdfGS hLgkG hGLhO GdfGS cakG hGTLY GdfGS bdHkG s
(3BNQgG (B:s
(3aNOeJg JSY MLL aeG bGd dTF bW UfYJ CSCJ hdG TeeJ QGFMg bW eSckG hdG YfHQ GWjH ef QGFMg QShd Gddg Udi Gddg Ydjg hSde BNQ GdGQHYjf GdYGdjGJ GdEHOGd GdJSGYjGJ ddHNGQi heSde s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs